Cervical impairments in subjects with migraine or tension type headache: an observational study - del Blanco Muñiz, Jose Ángel; Sánchez Sierra, Alberto; Ladriñán Maestro, Arturo; Ucero Lozano, Roberto; Sosa-Reina, María Dolores; Martín Vera, Daniel (Frontiers in neurology, 2024)
The aim of this investigation was to compare the thickness of the deep local muscles in the neck region, as well as local and widespread sensitivity and functionality, between individuals with migraine, Tension-Type Headache (TTH), and healthy controls. To date, we know that the onset of migraine and TTH share similar pathophysiological pathways. Nevertheless, there may be some anatomical and functional differences which would explain why clinicians may obtain variable results when treating both pathological entities with similar or equal approaches. An observational study was conducted in accordance with STROBE guidelines. The flexor longus colli and multifidus, two neck-stabilizing muscles, were measured using B-mode ultrasound imaging. The upper trapezius, masseter, temporalis, tibialis anterior, and median nerve all underwent bilateral pressure-pain threshold (PPT) assessments. Ninety participants were enrolled in the study. All subjects were equally divided into TTH, migraine and control groups. The PPT values exhibited lower thresholds in patients with TTH than both migraine and healthy participants. Specifically, in the temporal muscle on both sides, patients with TTH exhibited a significantly lower threshold ( < 0.001)than both migraine and healthy participants. Patients with TTH displayed significantly lower thresholds in both upper trapezius muscles (right: < 0.001; left: = 0.001). Similar results were obtained for the tibialis anterior PPTs from both sides ( = 0.001 in both). However, both clinical groups exhibited lower thresholds than the healthy subjects ( < 0.001). In multifidus muscle cross-sectional area (CSA), no statistically significant differences were found between migraine patients and healthy subjects, both in relaxation and contraction (right; > 0.05 and > 0.05; left: > 0.05 and > 0.05). However, patients with TTH exhibited a smaller CSA than both migraine patients and healthy controls in multifidus relaxed and contracted state (right: < 0.001 in both relaxed and contracted multifidus; left: = 0.001 and < 0.001, respectively). Similar results were obtained for the left longus colli muscle in both relaxation and contraction for patients with TTH and migraine compared with healthy subjects ( = 0.001 and < 0.001, respectively, for muscle relaxation and < 0.001 for muscle contraction). However, no significant differences were observed between patients with TTH and migraine ( < 0.05 in both relaxation and contraction). In the right longus colli, TTH and migraine patients had a significantly smaller CSA during contraction than healthy subjects ( < 0.001 in both comparisons). In the craniocervical flexion test, both groups of patients with TTH and migraine showed significantly lower values than healthy subjects ( < 0.001 in both comparisons). However, no significant differences were found between patients with TTH and migraineurs ( > 0.05). The findings provide a significant message for clinicians since anatomical and functional impairments were shown in patients with TTH and migraine. This study corroborates a lack of strength and smaller CSA in both clinical groups compared to controls. Therefore, strengthening programs may be addressed successfully for people with these pathological entities. To be more accurate, according to PPTs and CSA lower values in patients with TTH compared to migraine and controls, manual therapy approaches to desensitize craniocervical soft tissues and exercise therapy to increase endurance of deep cervical muscles may become meaningful especially in subjects with TTH. Nevertheless, in order to distinguish precisely between patients with TTH and migraine, different diagnostic strategies may be used in the future to describe these populations in further detail, which will assist health professionals in a more accurate treatment selection.